Analisis Faktor-Faktor yang Memengaruhi Purchase Intention Selama Pandemi Covid-19: Studi Pada Konsumen Susu Steril di Jakarta - Serin Sabrinada; Andi Muhammad Sadat; Rahmi (Jurnal Bisnis, Manajemen, dan Keuangan, 2022)
The spread of the Coronavirus during the pandemic has caused an increase in consumer purchase intention for health products such as sterilized milk. This is expected influenced by several causes such as electronic word of mouth, panic buying, and brand image. The purposes of this research are: 1) To determine the influence of electronic word of mouth on the purchase intention of Bear Brand products during the Covid-19; 2) To determine the effect of panic buying on the purchase intention of Bear Brand products during the Covid-19 pandemic, 3) To determine the influence of brand image on purchase intention of Bear Brand product during the Covid- 19 a survey of Jakarta citizens. Method of collecting data using survey method with an instrument in in Jakarta the form of a questionnaire. The object of this study is to at least 180 respondents from consumers of Bear Brand. Data analysis using SPSS version 25 and SEM Lisrel version 8.8 to process research data. The results of hypothesis testing show that electronic word of mouth has a significant positive effect on purchase intention. Panic buying has a significant positive effect on purchase intention. Brand image has a significant positive effect on purchase intention. Penyebaran virus Corona selama pandemi menyebabkan purchase intention konsumen meningkat terhadap produk yang baik untuk kesehatan seperti susu steril. Hal tersebut di duga di pengaruhi oleh beberapa penyebab seperti electronic word of mouth, panic buying dan brand image. Jenis penelitian yang digunakan dalam penelitian ini adalah metode kuantitatif. Tujuan penelitian ini adalah menganalisis faktor-faktor yang memengaruhi purchase intention konsumen susu Bear Brand selama pandemi Covid-19 di DKI Jakarta. Pengumpulan data dilakukan dengan metode survei dan instrumen yang digunakan berupa kuesioner. Objek penelitian ini sebanyak 210 responden dari konsumen susu Bear Brand di Jakarta yang pernah mengonsumsi susu Bear Brand minimal sekali selama pandemi Covid-19. Analisis data menggunakan SPSS versi 25 dan SEM 8.8 dari software Lisrel untuk mengolah data hasil penelitian. Hasil pengujian hipotesis menunjukkan electronic word of mouth berpengaruh positif dan signifikan terhadap purchase intention. Panic buying berpengaruh positif dan signifikan terhadap purchase intention. Brand image berpengaruh positif dan signifikan terhadap purchase intention.